PEMBELAJARAN BERBASIS MEDIA TIKTOK DALAM PENERAPAN BUDAYA MALU PEMBELAJARAN DARING SISWA KELAS V SEKOLAH DASAR - Tsalitsa Muzdalifah; Fitriana Fitriana (Intiqad: Jurnal Agama dan Pendidikan Islam, 2022)
Technology cannot be separated from everyone's lives with the development of technology, the greater the influence of the world, both negative and positive, a person must be able to keep up with technological developments.  The use of technology must be optimal, for example in the world of technology education, the available applications can be utilized very well in order to help in the learning process. The purpose of the study is to find out that the tiktok application can be used for cultural education of shyness of students. The method used is a descriptive qualitative research method with interview data analysis techniques, observation and documentation. The results of tiktok media in the application of shame culture get positive results students do not follow bad deeds such as dancing, using inappropriate words, students use the tiktok application to learn to draw, sing, and make rhyme videos, poems and others.